Strategi Pemberdayaan Petani Dalam Pengembangan Bawang Merah (Studi Kasus Desa Pajeng Kecamatan Gondang Kabupaten Bojonegoro) - Rendarwati, Rendarwati; Lestari, Eny; Widiyanto, Widiyanto (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to analyze the role of stakeholders in empowering the development of shallot agribusiness in Pajeng Village, Gondang District, Bojonegoro Regency. Evaluate the empowerment process for the development of shallot agribusiness in Pajeng Village, Gondang District, Bojonegoro Regency, and determine the development strategy for shallot Agribusiness in Pajeng Village, Gondang District, Bojonegoro Regency. Pajeng Village, located in Gondang District, Bojonegoro Regency, has significant agricultural potential, with the main focus on shallot production. Shallots are not just an agricultural crop, they are the backbone of the economy for local communities. The success of shallot production not only affects farmers' income, but also determines the economic stability and welfare of the Pajeng Village community as a whole. The importance of shallots in the local economic structure creates its own challenges and opportunities. Even though it is a superior commodity, farmers in Pajeng Village still face various obstacles in marketing their products. Price variability, limited markets, and hampered market accessibility are the main obstacles that affect farmers' ability to obtain optimal profits from their shallot harvest. Through case studies in Pajeng Village, it is hoped that solutions can be found that are appropriate to the local context, encourage the application of sustainable technology, and increase farmers' access to markets. The strategy for empowering farmers in developing shallot agribusiness is not only about increasing productivity but also establishing a strong foundation for sustainable economic and social development of Pajeng Village. There is so much interest in farmers developing shallot plants and the problems faced by farmers, researchers want to know the development of the Agribusiness system that has been going on so far. So it can be known how big the farming business is in developing shallot agribusiness. This causes researchers to intend to find out what strategies are used in developing shallot agribusiness. So this research is entitled